The Influence of Self-Efficacy, Organizational Culture and Spirituality on Work Happiness in Public Companies - Hidayani Syam; Yusuf Ronny Edward; Helmi Ali; Harfiahani Indah Rakhma Ningtyas; Roikhan Mochamad Aziz (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
The purpose of this study is to ascertain how organizational culture, workplace spirituality, and employee self-efficacy affect pleasure at work. Using the non-probability sampling method, a sample of 300 employees from three different organizations was taken. The measurement tools SHAW (the abbreviated version of HAW), FOCUS (First Organizational Culture Unified Search), GSE (General Self-Efficacy), and SAW (Spirituality in the Workplace) are modified by the author. Confirmatory factor analysis (CFA) techniques are used to test the validity of measuring instruments, and multiple regression analysis techniques are used to analyze data. According to the study's findings, corporate culture, workplace spirituality, and employee self-efficacy all have a big impact on how happy employees are at work. Only four variables support from organizational culture, connectedness and purpose in the workplace from spirituality in the workplace, and self-efficacy have a substantial impact, according to the value of the regression coefficient. It is hoped that it will be essential to examine and develop the scale once more for additional research, as well as to include a number of other demographic parameters including position and salary.